On the Relationship Between Job Involvement and Central Life Interest - Mitchell, Vance; Baba, Vishwanath; Epps, Timothy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
The present study investigates the relationship between job involvement (JI) and central life interest (CLI) for a sample of automobile workers chosen from three organizational levels containing unskilled employees, skilled workmen and fore-men. Possible associations of job involvement and work as the«  Central Life Interest » with job levels in the occupational hierarchy, age of the individuals and the length of employment were also explored. The results disconfirmed the hypothesized positive relationship between JI and CLI. In fact a low but significant negative relationship was obtained between JI and CLI. Job levels, age and length of employment were found to hâve negligible influence on both JI and CLI. On the basis of the obtained results, directions for future research are indicated.